2017
DOI: 10.1002/pro.3208
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐unique fold in the Rousettus bat coronavirus HKU9

Abstract: The coronavirus nonstructural protein 3 (nsp3) is a multifunctional protein that comprises multiple structural domains. This protein assists viral polyprotein cleavage, host immune interference, and may play other roles in genome replication or transcription. Here, we report the solution NMR structure of a protein from the "SARS-unique region" of the bat coronavirus HKU9. The protein contains a frataxin fold or double-wing motif, which is an α + β fold that is associated with protein/protein interactions, DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Future mutations or recombination events of SL-CoV-WIV1 could increase virulence and the likelihood of spillover of this viral strain as a related SL-CoV-WIV16 viral mutation has already been identified with greater nucleotide similarity with SARS-CoV GZ0 human isolate from 2003 SARS outbreak. Similarly, HKU4-CoV and NL140422-CoV are capable of binding to human DPP4 without adaptation of the spike protein and pose a zoonotic risk due to possible accumulation of adaptive mutations with persistent infections (289)(290)(291)(292). Another SARS-like virus, SHC014-CoV carrying the SHC014 spike mutation, and also found in Chinese horseshoe bats, has the potential to enter via ACE2 and, importantly, showed that immune-therapeutic and prophylactic modalities failed to stop the infection in a mouse model (293).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future mutations or recombination events of SL-CoV-WIV1 could increase virulence and the likelihood of spillover of this viral strain as a related SL-CoV-WIV16 viral mutation has already been identified with greater nucleotide similarity with SARS-CoV GZ0 human isolate from 2003 SARS outbreak. Similarly, HKU4-CoV and NL140422-CoV are capable of binding to human DPP4 without adaptation of the spike protein and pose a zoonotic risk due to possible accumulation of adaptive mutations with persistent infections (289)(290)(291)(292). Another SARS-like virus, SHC014-CoV carrying the SHC014 spike mutation, and also found in Chinese horseshoe bats, has the potential to enter via ACE2 and, importantly, showed that immune-therapeutic and prophylactic modalities failed to stop the infection in a mouse model (293).…”
Section: Discussionmentioning
confidence: 99%
“…Another SARS-like virus, SHC014-CoV carrying the SHC014 spike mutation, and also found in Chinese horseshoe bats, has the potential to enter via ACE2 and, importantly, showed that immune-therapeutic and prophylactic modalities failed to stop the infection in a mouse model ( 293 ). The Hong Kong University 9 (HKU9) virus also has a close similarity with sections of the SARS-CoV and the Wuhan SARS-CoV-2 within the receptor-binding domain for ACE2 and is also widely distributed in diverse species including Rousettus leschenaultii Desmarest, Hypostomus commersonii Valenciennes, Eidolon helvum Kerr, and R. aegyptiacus , from Asia to Africa ( 19 , 291 , 294 ). Whether diversity of human ACE2 increases the potential for new zoonotic transmission of viruses with similarity to SARS-CoV and SARS-CoV-2, or as yet unidentified ACE2-binding viruses, needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the two previous domains, SUD-C is the shortest in length domain (~ 60-70 amino acids) and has a frataxin-like or a double-wing motif α/β fold, consisting of five antiparallel β sheets, packed against two α helices (Johnson et al 2010;Chatterjee et al 2009;Tan et al 2009). The proposed function of SUD-M and SUD-C is that of binding of G-quadruplex forming RNA (Hammond et al 2017). It has also been reported that SUD-C from bat coronavirus has DNA and metal ion-binding properties (Staup et al 2019).…”
Section: Biological Contextmentioning
confidence: 99%
“…There are some notable differences between tissue tropism of the HCoVs. Analysis of structural similarities and structural differences between HCoVs species could advance the understanding of SARS-CoV-2 pathogenesis [ 8 12 ].…”
Section: Introductionmentioning
confidence: 99%